2022
DOI: 10.1093/noajnl/vdac022
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity does not significantly affect outcomes in brain metastasis patients treated with surgery

Abstract: Background Brain metastasis quantity may be a negative prognostic factor for patients requiring resection of at least one lesion. Methods We retrospectively reviewed patients who underwent surgical resection of brain metastases from July 2018 to June 2019 at our institution, and examined outcomes including overall survival (OS), progression free survival (PFS) and rates of local failure (LF). Patients were grouped according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Rastogi et al reported that 80% of their study population had multiple brain lesions [ 14 ]. Yang et al have discussed in their paper that having multiple brain lesions has been considered a negative prognostic factor in patients having brain metastasis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rastogi et al reported that 80% of their study population had multiple brain lesions [ 14 ]. Yang et al have discussed in their paper that having multiple brain lesions has been considered a negative prognostic factor in patients having brain metastasis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%